PENGARUH PROFESIONALISME DAN KETERAMPILAN PERAWAT TERHADAP MUTU PELAYANAN KEPERAWATAN RUMAH SAKIT - Pujiastuti, Endah; Purwadhi, Purwadhi; Restiani Widjaja, Yani (Yayasan Healing and Healthcare Education, 2023)
The quality of nursing services, as an indicator of the quality of health services, is a key element that influences public perceptions of the image of health service institutions. The importance of the role of professional nursing services in hospitals is very large, considering that nursing as a profession has the largest number of workers in the hospital environment, they are closest to patients, and also interact with families. The aim of the research was to determine the factors that influence the quality of nursing services at Mitra Anugerah Lestari Cimahi Lestari General Hospital. Method; This is a quantitative analytical cross sectional correlation research. The population in this study was 125 nurses at Mitra Anugerah Lestari Cimahi Hospital. The sample used was 104 people. Results; Most of the respondents were considered professional nurses, namely around 56.7% and skilled nurses, namely around 55.8%. Conclusion; The professionalism and skills of nurses influence the quality of nursing services with a sig value of 0.007. Suggestion; Developing strategies to improve interprofessional communication and coordination can optimize overall nursing service outcomes